A damage mechanics model for low-velocity impact damage analysis of composite laminates. (6th March 2017) - Li, N.; Chen, P.H.; Ye, Q.
ABSTRACT: A method was developed to predict numerically the damage of composite laminates with multiple plies under low-velocity impact loading. The Puck criterion for 3D stress states was adopted to model the intralaminar damage including matrix cracking and fibre breakage, and to obtain the orientation of the fracture plane due to matrix failure. According to interlaminar delamination mechanism, a new delamination criterion was proposed. The influence of transverse and through-thickness normal stress, interlaminar shear stress and damage conditions of adjacent plies on delamination was considered. In order to predict the impact-induced damage of composite laminates with more plies quickly and efficiently, an approach, which can predict the specific damage of several plies in a single solid element, was proposed by interpolation on the strains of element integration points. Moreover, the proposed model can predict specific failure modes. A good agreement between the predicted delamination shapes and sizes and the experimental results shows correctness of the developed numerical method for predicting low-velocity impact damage on composite laminates.